Patients with polymyositis or dermatomyositis have reduced grip force and health-related quality of life in comparison with reference values: an observational study - Regardt, M.; Welin Henriksson, E.; Alexanderson, H.; Lundberg, I. E. (Rheumatology (Oxford), 2011)
OBJECTIVES: The aims of this study were to investigate hand function in PM and DM patients and compare this with reference values in healthy individuals and also to investigate if hand function correlated with activity performance and health-related quality of life. METHODS: An observational cross-sectional study was performed in 18 women and 13 men with PM or DM with established disease. Grip force and hand mobility were assessed by Grippit and Escola Paulista de Medicina-Range of Motion scale. Activity performance was measured with myositis activities profile and health-related quality of life by short form-36 (SF-36). RESULTS: Women and men with PM and DM with mean disease duration of 6.8 (5.5) years had a significantly lower grip force than gender- and age-matched healthy individuals (women 71% and men 60%). They also had significantly lower mean values in all dimensions of the health-related quality of life instrument SF-36 compared with the Swedish population. In patients with PM and DM, the grip force correlated significantly with the ability to perform domestic activities. In women with PM and DM, the grip force correlated significantly with the health-related quality of life dimensions vitality and mental health. There were no significant differences between patients with PM and DM regarding grip force, hand mobility, activity performance or health-related quality of life. CONCLUSIONS: Patients with PM or DM have reduced grip force that could influence activity performance and health-related quality of life.